40 Transcatheter paravalvular leak closure; a single centre experience. (5th October 2017) - Tanner, R; Hassan, S; Ryan, N; Murphy, N; Campbell, P; Margey, R; Walsh, K; Blake, G; Casserly, IP
Abstract : Introduction: Significant paravalvular leak (PVL) is estimated to occur in at least 1–2% of patients undergoing surgical aortic and/or mitral valve replacement, and 3–4% of patients undergoing percutaneous aortic valve replacement (TAVR). Surgery for repair of PVL is associated with a 30-day mortality of approximately 10%. Percutaneous closure of PVL has emerged as an alternative to surgical repair. Methods: Using a prospective registry, we sought to examine the clinical outcomes of patients treated with percutaneous closure of PVL at a tertiary referral hospital in Ireland. Results: A total of 21 patients (mean age 68 ±13 years, 76% male) were treated for PVL. Heart failure (HF) and haemolysis (HL) were the presenting symptoms in 62% and 24% of patients, respectively. The remaining 14% of patients presented with both HF and HL. Of the 21 prosthetic valves treated, 9 were in the mitral position, and 12 were in the aortic position. A total of 26 PVL procedures were performed in the 21 patients (mean of 1.2 procedures/patient). The mean number of plugs used per patients was 1.9 (range 0–4). There was one (3.8%) major adverse procedural complication (stroke) and two minor (7.7%) procedural complications (both vascular access complication treated with endovascular techniques). Among patients with HF as the presenting symptom (n=16), the mean NYHA class before and after percutaneous PVL closure was 2.6 ±0.62 versus 1.5 ± 0.63. None of these patients have required repeat surgery over a median follow-up of 20 months (IQR 9.5–32). Among patients with HL, clinical success was achieved in 2 of 5 patients (40%). A total of 6 deaths (28%) occurred in the patient cohort over a mean follow-up of 22 ±13.4 months. Thirty-day mortality was 0%. Figure 1 shows the Kaplan Meier Estimate of survival. Conclusions: Patients with PVL represent a high-risk patient cohort. Percutaneous PVL offers a safe alternative to surgical PVL repair, and appears particularly effective in those patients who present primarily with HF as their presenting symptom.